Penggunaan Strategi Mastery Learning Dalam Pembelajaran Fikih Untuk Meningkatkan Keterampilan Siswa Dalam Ibadah Shalat Kelas VII F Di MTs Cikajang Garut - Maria, Anly; Taufikurrohim, Regi Dikri (STAI Al-Musaddadiyah Garut, 2025)
This research discusses the use of Mastery LearningStrategies in learning jurisprudence to improve students' skills in class vii f prayer at MTs Cikajang Garut. students' skills in prayer are the driving force within the individual that gives rise to learning activities that ensure the continuity of learning activities and that provide direction to learning activities so that the desired goals will be achieved. however, in reality, students' skills in praying in class vii f mts cikajang garut are still relatively low, this is proven by the results of pre-research observations which show that only around 26% of 35 have skilled learning skills so that stimulus is needed, one of which is using the Mastery Learningstrategy. The objectives of this research are 1) to describe the use of the Mastery Learningstrategy in the learning of fiqh class vii f at MTs Cikajang Garut; 2)describe students' skills in praying in class vii f at MTs Cikajang garut; 3) describe the Mastery Learningstrategy in learning fiqh to improve students' skills in praying in class vii f at MTs Cikajang garut. The method used is classroom action research (ptk). data collection techniques include observation, questionnaires, interviews and documentation. the data analysis technique in ptk only uses simple statistical formulas to find the average value and percentage of learning completeness. The results of this research show that there was an increase in students' skill activities in prayer in cycle i to 51%, then there was an increase again in cycle ii to 100%. it can be seen that there is an increase in students' skills in prayer by 25% from pre-cycle to cycle i and by 49% from cycle i to cycle ii. so, overall there was an increase in students' learning skills in prayer with a significance of 74% from pre-cycle to cycle II Keywords; Mastery Learningstrategy; jurisprudence learning; prayer worship